1997
DOI: 10.1002/(sici)1099-1387(199703)3:2<110::aid-psc88>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Characterization of the 1-Aminocyclobutane-1-carboxylic Acid Residue in Model Peptides

Abstract: A series of N- and C-protected, monodispersed homo-oligopeptides (to the dodecamer level) from the small-ring alicyclic C alpha, alpha-dialkylated glycine 1-aminocyclobutane-1-carboxylic acid (Ac4c) and two Ala/Ac4c tripeptides were synthesized by solution methods and fully characterized. The conformational preferences of all the model peptides were determined in deuterochloroform solution by FT-IR absorption and 1H-NMR. The molecular structures of the amino acid derivatives Z-Ac4c-OH and Z2-Ac4c-OH, the tripe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…The upfield resonance in CDCl 3 solution is unambiguously assigned to the urethane N(1)H proton 44. The second upfield resonance is assigned to the peptide N(2)H proton by analogy with the chemical shifts in the same halohydrocarbon and the spectroscopic behavior upon addition of the same perturbing agents of peptides from different types of C α,α ‐dialkylated glycines 18–21, 49, 50. In one case, a complete assignment of all NH protons was achieved from the correlated spectroscopy and rotating frame nuclear Overhauser effect spectroscopy spectra 50.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upfield resonance in CDCl 3 solution is unambiguously assigned to the urethane N(1)H proton 44. The second upfield resonance is assigned to the peptide N(2)H proton by analogy with the chemical shifts in the same halohydrocarbon and the spectroscopic behavior upon addition of the same perturbing agents of peptides from different types of C α,α ‐dialkylated glycines 18–21, 49, 50. In one case, a complete assignment of all NH protons was achieved from the correlated spectroscopy and rotating frame nuclear Overhauser effect spectroscopy spectra 50.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical and experimental studies of the preferred conformations of peptides characterized by the Ac n c ( n = 3–9) residues have been the subject of recent review articles and papers 13–21. In a close parallelism to the structural behavior of Aib (α‐aminoisobutyric acid or C α,α ‐dimethylglycine),13–16, 22–25 the prototype of C α,α ‐disubstituted glycines, it was shown that regular or slightly distorted β‐bend forms26–28 or 3 10 ‐helical structures29 are adopted as a function of main‐chain length and side‐chain size.…”
Section: Introductionmentioning
confidence: 99%
“…Although the average N‐C α ‐C′ (τ) bond angle of the achiral Ac 4 c tetrapeptide was reported to be widened to 114.7° from the normal angle 110–111°, the average N‐C α ‐C′ (τ) of 11 was a regular 111.9° (Table S4) . The distances between the Cγ atom and plane defined by C β , C α , and C β ′ of the amino acid residues in 11 were within the range of 0.001 to 0.419 Å, and their average was 0.191 Å, indicating that the cyclobutane ring is flatter than the puckered form.…”
Section: Figurementioning
confidence: 99%
“…The distances between the Cγ atom and plane defined by C β , C α , and C β ′ of the amino acid residues in 11 were within the range of 0.001 to 0.419 Å, and their average was 0.191 Å, indicating that the cyclobutane ring is flatter than the puckered form. The cyclobutane ring of residue (2) in conformer A, and those of residues (2) and (3) in conformer B were coplanar (Table S5) …”
Section: Figurementioning
confidence: 99%
“…7,8 Peptides with cyclic dAAs are more likely to adopt a helical structure, even those with short sequences. [9][10][11][12][13] These helical peptide foldamers have been reported to function as antimicrobial peptides, 14,15 peptide catalysts, 16,17 and drug delivery peptides. [18][19][20] In contrast, peptides composed of acyclic dAAs with two bulky substituents equal to or larger than ethyl groups are more likely to form extended planar C5 conformations.…”
mentioning
confidence: 99%